Description Of Risk Factors For Musculoskeletal Disorders In Workers In The Home Industry Drinking Water Darussalam Gontor Ponorogo - Ani Asriani Basri; Praja Satriamukti; Ratih Andhika Akbar Rahma; Dian Afif Arifah (Universitas Muhammadiyah Malang, 2023)
Background: Home Industry Air Minum Darussalam (AMIDAS) Gontor is the only industry that produces mineral water located in Ponorogo, East Java managed by the business unit Pondok Modern Darussalam Gontor Ponorogo. In general, the production process at AMIDAS Gontor is divided into three main activities; packaging, warehousing, and shipping. The three main activities of this work are still done manually by workers, so workers doing repetitive movements or incorrect work postures can pose a risk of Musculoskeletal Disorders (MSDs). Objectives: This study aims to describe the MSDs factor among workers in the Air Minum Darussalam (AMIDAS) Gontor household industry. Research Methods: This research is descriptive research. The population in this study is all workers in the Air Minum Darussalam (AMIDAS) Gontor who require 25 people with data collection techniques using the Quick Exposure Check (QEC) questionnaire and the Nordic Body Map (NBM) instrument.Results: The measurement results of the work posture describe related to the risk of MSDs showed that workers in the Air Minum Darussalam (AMIDAS) Gontor household industry majority as many as 7 people with a percentage (28%) experienced high complaints that received a level 4 action score. In addition, workers have experienced 12 minor complaints (48%), 5 moderate complaints (20%), and 8 high complaints (32%). The average complaints of MSDs in workers in the Home Industry Air Minum Darussalam (AMIDAS) Gontor the majority of which experienced high complaints are found on the back (65%), compared to the lowest complaints found in the left ankle (38%). Conclusion: To overcome the problem of work posture that occurs, it is recommended that the manager or manager of the company provide hand pallets so that they can be used to facilitate workers in doing their jobs, as well as implement a rolling system for workers. Keywords:Work posture, QEC, NBM, AMIDAS Gontor